2011
DOI: 10.1002/ffj.2063
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of pullulan films containing thymol

Abstract: Thymol displays strong activity against microorganisms that are of interest in clinical field and in food industry. Pullulan can form homogeneous films, which is an important property for its use as a coating material in the food industry. The present study determining the effect of thymol incorporated into a pullulan film against selected bacteria. The final content of thymol in the dried films ranged from 2.5 mg/cm 2 to 52.9 mg/cm 2 . The structure of the surface and cross-section of the films were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 55 publications
5
34
0
Order By: Relevance
“…Pullulan films are formed from extracellular polysaccharide produced by the fungus Aureobasisium pullulans, and when combined with thymol expressed strong inhibitory activity against Bacillus subtilis ATCC6633, Staphylococcus aureus ATCC25923, Salmonella enteritidis ATCC13076, and Escherichia coli ATCC25922 [77]. In this work, the authors also reported that the aroma of thymol introduced in the pullulan film was not perceptible after the skin of the mandarins had been peeled or after the film had been removed from the surface of apple.…”
Section: Rojas-graümentioning
confidence: 71%
“…Pullulan films are formed from extracellular polysaccharide produced by the fungus Aureobasisium pullulans, and when combined with thymol expressed strong inhibitory activity against Bacillus subtilis ATCC6633, Staphylococcus aureus ATCC25923, Salmonella enteritidis ATCC13076, and Escherichia coli ATCC25922 [77]. In this work, the authors also reported that the aroma of thymol introduced in the pullulan film was not perceptible after the skin of the mandarins had been peeled or after the film had been removed from the surface of apple.…”
Section: Rojas-graümentioning
confidence: 71%
“…Based on the images presented in Fig. c–f, it might be speculated that the addition of thymol to PLA/PCL led to changes in the structure of films . The higher the thymol content in the PLA/PCL blends, the more and larger were the micro‐voids that appeared in the film.…”
Section: Resultsmentioning
confidence: 97%
“…Thymol displays strong antimicrobial activity against natural spoilage bacteria and food borne pathogens, e.g. Salmonella typhimurium , Escherichia coli , Listeria monocytogenes , Bacillus cereus , and Staphylococcus aureus . Recently, films containing thymol have been prepared by a wide variety of raw materials, such as zein, gelidium corneum, pullulan, polypropylene, and low‐density polyethylene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pullulan is an important biopolymer compound have a repeated glucose unit linked as a (1/6) (Catley et al, 1986;Zajic and LeDuy, 1973). Pullulan containing materials with biocide agents have a good antibacterial properties (Gniewosz and Synowiec, 2011). In addition, it has an excellent physical properties, such as, solubility in water, anti-inflammatory, antithrombotic, anticoagulant and adhesive properties.…”
Section: Introductionmentioning
confidence: 99%